Aplikasi Test Pengajaran Bahasa Inggris Di Laboratorium Bahasa Polman Babel - Raihan Alghifari; Sidhiq Andriyanto; Sari Mubaroh (Jurnal Inovasi Teknologi Terapan, 2026)
This study aimed to develop a mobile-based English teaching test application used in the language Laboratory of Polman Babel. Before this study was conducted, the evaluation process of English learning still used paper-based tests, which required a long correction time and carried a risk of scoring errors. The developed application provided a solution by offering a digital testing system that displayed questions, received student answers, and automatically generated results. The research applied the Research and Development (R&D) method with a waterfall approach consisting of requirement analysis, system design, implementation, testing, and evaluation. The application was developed using the Flutter framework for the user interface and Laravel for data management on MySQL. The testing results showed that the application functioned properly and improved the efficiency of the assessment process while reducing correction errors. Therefore, this application was expected to serve as an innovative alternative to support the digitalisation of English learning assessment in higher education institutions